Thực trạng văn hóa nhà trường trong trường trung học cơ sở: Nghiên cứu trường hợp tại phường Diên Hồng và phường Hòa Hưng, thành phố Hồ Chí Minh - Nguyễn Thị Ngọc Huyền, Nguyễn Thị Ngọc Huyền; Nguyễn Thị Quốc Minh, Nguyễn Thị Quốc Minh (Tạp chí Giáo dục, 2026)
In the context of Vietnam’s education system’s focus on developing a healthy and sustainable school environment, this article presents the results of a survey on school culture conducted at junior high schools in Dien Hong and Hoa Hung wards, Ho Chi Minh City, involving 29 administrators and 116 teachers from four public schools. The results show that most cultural elements were rated as good, notably the friendly school atmosphere, the professional qualities and competence of the teaching staff, and the maintenance of the value of “promoting tradition and inheritance”. However, the value of “empowerment” received the lowest rating; further flexibility in teaching organization and the development of student autonomy are still needed. Based on this, the article proposes prioritizing improvements to mechanisms that empower students and encourage proactiveness in educational activities, aiming for the stable and comprehensive development of the school. The results provide further practical evidence to support policy planning for school culture development in the current context.